HEALTH STATUS AND PRODUCTIVITY ANALYSIS OF RURAL FARMING HOUSEHOLDS IN ABIA STATE, NIGERIA - Raphael Ndubuisi ECHEBIRI; Daniel Chinedu NWAOGU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study analyzed the relationship between farmers’ health status and their productivity levels in Abia state. A multi-stage sampling technique was adopted in collecting data for this research, thus, a total of 1080 farmers were selected. Simple descriptive statistics, the total factor productivity and ordinary least squares methods were employed in the data analysis. A mean productivity value of 1.895 implies that an average farmer made about 89 kobo for every one naira invested. Healthy farmers had a higher mean productivity (2.1246) than non-healthy farmers (1.9018). The regression model gave an R2 of 0.594, 0.458 and 0.892 implying that 59.4%, 45.8% and 89.2% changes in the productivity of the three groups (pooled, healthy and non-healthy farmers) were accounted for by changes in the explanatory variables included in the model. The study showed that healthy farmers with access to appropriate inputs (including knowledge, land, tools, fertilizer, and seeds) had higher productivity and earned good incomes than non-healthy farmers, thus health improvement strategies granted to the farmers by government will allow them to thrive nutritionally, acquire more assets (including health), and become more resilient. It is also recommended that that land be made available to smaller farms to enhance increased overall production.